The intratumor microbiota and thyroid cancer: a review - Shan Liu; Xiaoliang Xiong; Tingting Hao; Xue Shi; Yinlong Zhao (Frontiers in Endocrinology, 2025)
Thyroid cancer is a prevalent malignancy with a rising global incidence, driven by factors such as genetic mutations, environmental influences, and gender differences. Despite advancements in diagnostic techniques and treatments, effective therapies for advanced or iodine-refractory thyroid cancer remain limited. Recent discoveries have challenged the long-held belief that tumors are sterile, revealing the presence of intratumor microbiota in various cancers. Intratumor microbiota significantly impact cancer development, immune reactions, and the effectiveness of treatments. This review examines the emerging evidence of intratumor microbiota in thyroid cancer, emphasizing their potential roles in tumor development. We also examine the origins and diversity of these microbial communities and investigate the mechanisms through which they might affect thyroid cancer progression. Understanding the complex interactions between intratumor microbiota and thyroid cancer could inform the development of novel diagnostic tools and therapeutic strategies to improve patient outcomes.